Histopathological study of breast lesions - Ranjitsingh Sulhyan, Kalpana; Rameshrao Anvikar, Arti; Mahamadisak Mujawar, Imran; Tiwari, Hitesh (International Journal of Medical Research and Review, 2017)
Objectives: To study the histopathological features of neoplastic and non neoplastic lesions of breast. To correlate the pathological findings with clinical parameters. Design and methods: We have studied total 161 cases of breast lesions over a period of two years in our institute. The specimens were received in histopathology section of our department. Detailed gross examination of specimens was done followed by fixation, thorough sampling, and tissue processing. The different lesions were studied by histopathological examination and analysed. Neoplastic lesions were classified according to the WHO classification (2012). Results: Out of the 161 cases, 128 cases had neoplastic lesions and 32 cases had non-neoplastic lesions, and one case had coexistent neoplastic and nonneoplastic lesions. Two cases had dual neoplastic lesions. Out of the total 129 cases with neoplastic lesions, 76 cases had benign breast tumors, 53 cases had malignant breast tumors, and 2 cases had precursor lesions. Fibroadenoma was the most common benign tumour with 60 cases. Invasive carcinoma no special type was the most common malignant tumour with 43 cases. Special subtypes of invasive carcinoma found in our study were metaplastic carcinoma (3 cases) and mucinous carcinoma (1 case). The most common nonneoplastic lesion was mastitis with 12 cases, followed by duct ectasia and fibrocystic change. There were 4 cases of gynaecomastia. All the tumors involved upper outer quadrant most frequently. The benign tumors were most frequent in second, third and fourth decades, malignant tumours were seen beyond 4th decade. The nonneoplastic lesions were common in 4th decade. Conclusion: Histopathological study is important in the management of breast lumps